Communication Accommodation of Raja Ampat Students in Yogyakarta for Dispelling Negative Stereotypes - Tyas Adinisa; Yanti Dwi Astuti (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2024)
In the realm of intercultural communication, the necessity of adjusting becomes apparent for fostering harmonious interactions. However, not everyone adeptly navigates these adjustments, leading to instances of discord. Some cases emerge among Papuan students in Yogyakarta, where some are labeled as disruptive, thereby contributing to negative stereotypes held by the broader Yogyakarta community. This study delves into the accommodation communication strategies employed by students from Raja Ampat in Southwest Papua as a proactive response to counteracting these negative stereotypes. Employing a qualitative approach, the research incorporates in-depth interviews, participatory observation, and documentation methods for data collection. The analysis follows a descriptive research method, offering insights into the communication accommodations devised by Raja Ampat students to address negative stereotypes prevalent in Yogyakarta. The findings highlight substantial convergence efforts by Raja Ampat students, spanning language usage, communication styles, behaviors, and communal activities. Concurrently, the students also engage in deliberate divergences to preserve their cultural identity. Through these adjustments, Raja Ampat students foster positive relationships, enhance interactive experiences, and contribute to a more adaptable perspective among the people of Yogyakarta regarding information surrounding negative stereotypes.